A measurement of cosmic-ray positron and negatron spectra between 50 and 800 MV - Daugherty, J. K.; Hartman, R. C.; Schmidt, P. J. (1975)
A balloon-borne spark chamber magnetic spectrometer has been used to measure the spectra of cosmic-ray positrons and negatrons at energies between 50 and 800 MV. The data reported here were obtained during two flights from Fort Churchill, Manitoba, in July 1972. The present results indicate that the dominance of negatrons from primary sources, found in earlier experiments above 200 MV, extends down to at least 50 MV. Solar modulation of the positron component is found to be consistent with that of the total electron spectrum, assuming that the positron component is entirely attributable to collisions between cosmic-ray nuclei and the interstellar gas.